Impact of Restructuring on Efficiency of Vietnam's Commercial Banks - Tran, Hoang Ngan (University of Economics Ho Chi Minh City, 2023)
The paper presents research on restructuring of Vietnam's system of commercial banks by implementing a three-stage DEA/SFA approach to estimate of impact of the restructuring process on banking efficiency. The empirical findings show that rises and falls in banking efficiency are irregular because the restructuring process has not completed and that some banks gain higher efficiency scores while others, especially those affected by low performance of merged banks, witness sharp falls.